ASSISTANCE IN THE DEVELOPMENT OF THE CREATIVE ECONOMY SECTOR IN TIDORE NORTH MALUKU - Runtunuwu, Prince Charles Heston; Taghulihi, Betly (Media Inovasi Pendidikan dan Publikasi, 2024)
City Tidore has the potential for micro and small businesses Which very potential For developed. Development of this sector requires cooperation and participation of all stakeholders, including local communities. One of the programs that can help the community is the creative economy sector development program launched government. Objective activity Devotion to public Which held by Khairun University Ternate is For increase motivation public to prepare products for micro and small businesses Which optimal For visitors so that can bring positive impacts, both from an economic aspect, social culture, nor environment Which sustainable. Activity This held through series of FGD Forum activities with material about creative economy development strategy Which next with session discussion. Results Which obtained is increase knowledge And outlook creative economy actors in the City of Tidore Islands.